(3eSGdc GdCagGe Edi BjGJ GdCMcGes - (3GdHZOGOj, GdcGXej, GdLhGO GdHZOGOj, LhGO Hf SYO Hf LhGO, J (B1065(3g`s
(3ChdgG (B:s
(3bGd GdTjN GdWhSj aj JaSjQg GdehShe HGdHjGf hGYde Cf GdQhGjI XGgQI aj CNHGQ CUMGHfG HCf JaSjQ GdbQBf dG jLhR EdG HGdCeQ dUMjM Yf GdfHj (B...s
(3BNQgG (B:s
... (3EdG Cf eKdg EfeG jJCJi ef CUMGH GdfahS (B..(3bQHfG Edi QMeJc hHGYO HjffG hHjf eYUjJc hYGedfG aj CaYGdfG HGdMSf hVGYa KhGHfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGdCYdGe , ddRQcdj (B2\142s
(3EjVGM Gdecfhf , ddHZOGOj (B2/472s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs